Handbook of research on disaster management and contingency planning in modern libraries - Decker, Emy Nelson 1978-; Townes, Jennifer A. 1981- (Advances in library and information science (ALIS) book series, 2016)
"This book brings together the latest scholarly research, theories, and case studies to investigate the scale and types of disasters that can impact a library"--Provided by publisher.